P1646SURVIVAL OF KIDNEY TRANSPLANTS ACCORDING TO PRESENCE OF HLA ANTIBODIES WHEN DONORSPECIFIC ANTIBODIES ARE SCREENED DURING POSTTRANSPLANT FOLLOW-UP. (6th June 2020) - Derad, Inge; Busch, Johanna; Nitschke, Martin; Ziemann, Malte
Abstract: Background and Aims: Posttransplant kidney survival depends on several risk factors. A careful immunogenetic matching and the absence of HLA donor specific antibodies (DSA) seem to determine the longevity of the transplant. Method: Screening the presence of donor specific HLA antibodies in our posttransplant outpatients was implemented in 2010 (every 6 months in case of DSA free patients for two years, then yearly, and every 3 months in case of DSA + patients for two years, then twice a year). At the same time a treatment protocol was implemented, omitting reduction of immunosuppressive drugs in case of newly detected DSA, and most important with preventing steroid withdrawal in this case.The present single center study reports the long-term survival and kidney function from patients undergoing HLA-screening after transplantation between 2010 and 2016 with a follow-up until 2018. Using a Kaplan-Meier analysis patients without HLA antibodies (no HLA-ab), with HLA antibodies but without DSA (NDSA), and with donor-specific HLA antibodies (DSA) were compared by logrank-testing. Results: A full dataset was obtained from 318 patients. The mean overall survival (patients and organ function) didn´t differ between the three groups, p=0.318: no HLA-ab 7.2 years (95%confidence interval 6.7;7.6), NDSA 6.6 (5.9;7.2), DSA 6.8 (6.1;7.5), overall 7.0 (6.6;7.3), events are given in Table1. Whereas the mean patient survival didn´t differ between the groups (p=0.715), the mean death-censored graft survival differed significantly, p=0.008, with a reduced transplant survival in the patients with HLA antibodies but without donorspecific antibodies: no HLA-ab 8.0 years (95%confidence interval 7.7;8.3), NDSA 7.0 (6.4;7.6), DSA 7.6 (7.1;8.2), overall 7.7 (7.4;8.0), numbers are given in Table1. Conclusion: In conclusion, the presence of HLA antibodies was associated with a reduced transplant survival. Patients with HLA antibodies had a worse survival than patients with DSA undergoing HLA screening with a personalised immunosuppressive regimen. Immunosuppressive regimen of the groups, as well as other known risk factors of graft survival have to be further analysed. The results of these multivariate analyses have to be awaited to determine whether the risk for graft loss inferred by HLA antibodies is independent from other factors.